Religious Freedom under Scrutiny - Bielefeldt, Heiner (Pennsylvania Studies in Human Rights Ser., 2019)
Religious Freedom Under Scrutiny argues that without freedom of religion or belief, human rights cannot fully address the needs, yearnings, and vulnerabilities of human beings and that marginalizing freedom of religion or belief would weaken the plausibility and legitimacy of the entire system of human rights.